The Use of Articles in Spoken and Written Discourse (Philologia, 2021)
This paper deals with a survey describing the students’ use of articles in a spoken register that was compared to the use of articles in a written register. The results showed that articles are generally more common in written than in spoken corpus. The definite article is almost twice as common as the indefinite article in the written register because it has a greater range of uses. Since in the current language teaching practice and theory the emphasis is put on the communicative language competence, it is important to decide how to best help students become proficient in the use of articles. Due to the small size of the corpus, the conclusions of the present study should be subjected to further re-examination and verification.
Keywords: students' usage of definite and indefinite articles; spoken and written register; grammar presentation